Prevalência de hipovitaminose D, caracterização do perfil metabólico e epigenético de pacientes fibrocísticos e efeito da suplementação com vitamina D3 - Paiva, Maria Paula de (2020)
Cystic fibrosis is a rare genetic disease that brings about a number of health metabolic issues for affected individuals. Fat-soluble vitamins’ absorption problems, especially vitamin D, have been reported amongst patients. Hypovitaminosis D may intensify the patient’s inflammatory response, provoke pulmonary exacerbations and worsen their prognosis. The vitamin D receptor gene (VDR) exerts a crucial role in vitamin D3 metabolism and genetic expression. This genetic sequence can be modulated by genotypic variability as well as epigenetic mechanisms, therefore producing distinct metabolic responses to vitamin D in different individuals. Genetic polymorphisms, as well as their influence on calcitriol deficiency and on its supplementation’s aftereffects, have been reported for the VDR sequence in the literature. However, there are no data concerning the effect of calcitriol supplementation upon VDR gene methylation profile in fibrocystic disease patients. Therefore, the aim of this study was to evaluate hypovitaminosis D and vitamin D3 supplementation outcomes in children and adolescents with cystic fibrosis. Characterization of this population’s metabolic profile was performed, as well as DNA methylation analysis and estimation of BsmI polymorphism (rs1544410) prevalence for the VDR sequence. A clinical trial involving 12 cystic fibrosis patients, both male and female, ranging from 8 to 12 years old, was carried out at the Hospital UniversitárioLauroWanderley, in João Pessoa - PB. Patients were submitted to biochemical and nutritional examinations, and whole blood samples were collected for DNA extraction as well as assessment of oxidative stress and inflammatory indicators. After determining hypovitaminosis D prevalence, four patients were submitted to vitamin D3 megadose supplementation and examinations were performed once more. Data were analyzed using the SPSS® Statistics 25.0 software for paired sample T-test, Mann-Whitney and Wilcoxon test calculations. Prevalence of serum 25-hydroxy vitamin D (25(OH)D) insufficiency/deficiency comprised 58,3% of the studied population, while 83,33% of them presented low height-to-age values. Significant differences were observed between individuals with sufficient 25(OH)D values in comparison to those with insufficiency/deficiency, with regard to blood sugar (p=0.02) and ALT serum levels (p=0.05), and uric acid (p=0.02). Amongst supplemented patients, an increase in 25(OH)D was observed (18,3 ng/dL to 34,1 ng/dL) without significant alterations in markers of renal and hepatic functions. No significant differences were observed in relation to inflammatory, oxidative and epigenetic profiles. Low intake of calcium, vitamin D3 and methyl donors such as B-complex vitamins, was prevalent, and the “b” allele was observed in six out of all patients from the insufficiency/deficiency group when compared to the homozygous “B” allele. In conclusion, DNA methylation did not affect VDR gene expression in relation to vitamin D serum levels in fibrocystic disease patients, and its supplementation was unable to modulate this epigenetic mechanism. It also did not influence the patients’ inflammatory or oxidative profiles, even though the supplemented individuals reached adequate serum concentration values for this vitamin.